Heat transfer measurement through building glass material - Norain, Chin (2013)
A method for the measurement of heat transfer of building glass material is presented. It is based on the use of a Data Acquisition designed to enable data collection of glass material from temperature reading. Preparation method include the circuit and software design.The glass material was test in 4 days during day time about 3 hour from 11.30 a.m until 1.30 p.m. From the result the time of maximum temperature and the minimum temperature can be observed. Based on Fourier's Law heat conduction formula the heat rate(Q- value) was calculated. Results in this project can be used in building industry in order to save energy consumption.